RecruBot : Designing an HR Chatbot - Nová, Denisa (2020)
The aim of this bachelor thesis is to design a chatbot named RecruBot that will inform potential candidates about the company’s job opportunities. This work includes well described finalized design of the chatbot, including its structure, functionalities and components. Necessary components for chatbot construction are researched and consequently discussed. The resulting design is then evaluated based on predetermined requirements and based on conducted interview with university students of various fields of study.